(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to reveal the reality of women’s empowerment at Tishreen University from the point of view of its workers, to reveal the differences in the opinions of female workers at Tishreen University about the reality of women’s empowerment in it according to the variables (college and academic qualification), the research sample included (156) female workers at Tishreen University for the academic year 2022/2023. Use the descriptive approach, To achieve the purpose of the research, a questionnaire was built consisting of (44) phrases that measure the reality of women’s empowerment at the university, distributed into five areas: (social empowerment, administrative empowerment, health and environmental empowerment, technological empowerment, and psychological empowerment). The results of the research showed that the reality of women’s empowerment at Tishreen University from the point of view of female workers came to an average degree, as well as the absence of a statistically significant difference between the average scores of the research sample of female workers at Tishreen University about the reality of women’s empowerment in it according to the college variable, and the existence of statistically significant differences according to the academic qualification variable in favor of university degree holders. The research also presented several proposals, including: diagnosing the most important obstacles that prevent women’s advancement, finding appropriate solutions to help them advance careers, and developing new mechanisms to increase the effectiveness of women’s involvement in community activities.